Ending the U.S. War in Iraq The Final Transition, Operational Maneuver, and Disestablishment of United States Forces-Iraq - Brennan, Richard R. Jr (RAND Corporation, 2013)
Ending the U.S. war in Iraq required redeploying 100,000 military and civilian personnel; handing off responsibility for 431 activities to the Iraqi government, U.S. embassy, USCENTCOM, or other U.S. government entities; and moving or transferring ownership of over a million pieces of property in accordance with U.S. and Iraqi laws, national policy, and DoD requirements. This book examines the planning and execution of this transition.